Effect of Intercropping on the Incidence of Sucking Insect Pests on Moth Bean [Vigna aconitifolia (Jacq.) Marechal] - Bairva, D K; Sharma, J K; Kumawat, K C (Annals of Arid Zone, 2016)
Short Communication